“Refugees” as a Misnomer: The Parochial Politics and Official Discourse of the Visegrad Four - Gruszczak, Artur (2021)
Attitudes towards migrants and refugees are created and reflected at the level of public policies, as well as in local communities which cultivate traditional approaches and a specific worldview. The refugee crisis in Europe in the mid-2010s showed how public opinion translated into voting behaviour and became a source of strength for nationalist anti-immigrant movements and parties across the continent. East-Central Europe was no exception, regardless of the absence of a long-term, massive inflow of refugees. Nevertheless, the migration crisis created a new political narrative which exploited deeply rooted resentments, complexes, and fears. This article aims to analyse the official policy responses to the refugee crisis in the four East-Central European countries: Poland, Hungary, Slovakia, and the Czech Republic, which together constitute the so-called Visegrad Four. It puts the emphasis on the discriminatory practice of misnaming the refugees, which became deeply anchored in the political discourse of these countries. Based on a qualitative content analysis supplemented by the findings of public opinion polls, the argument developed in the article is that reluctant and defensive attitudes towards the refugees have been determined by the revival of parochialism as a radical reaction to the challenges of global trends and supra-local processes. The theoretical framing of the refugee problem is built on politicization, in connection with the concept of parochialism, seen from political and social perspectives, and the meaning of the use of the misnomer as a policy instrument. The article concludes that the migration crisis petrified traditional cleavages at the supra-local level, reinforcing simultaneously the sense of parochial altruism and hostility towards “the other.”